New linker systems for superior immobilized catalysts - Beele, Björn B.; Guenther, Johannes; Perera, Melanie; Stach, Michaela; Oeser, Thomas; Blümel, Janet (New journal of chemistry, 2010)
The rigid linkers E(p-C6H4PPh2)4 (E = Si, Sn) have been synthesized from the corresponding precursors E(p-C6H4Br)4 and immobilized by forming one (E = Si) or three (E = Sn) phosphonium groups that are attached to the silica support by electrostatic interactions. The remaining unquaternized phosphines are coordinated to Wilkinson-type Rh complexes. The catalyst immobilized by the rigid scaffold with three surface-bound phosphonium groups (E = Sn) displays superior catalytic activity and lifetime with respect to the hydrogenation of dodecene. This catalyst can be recycled 30 times in a batchwise manner under standardized conditions.
Gesehen am 04.01.2023